Signs of closeness and introspection in the poems of Paruyr Sevak's collection "Let there be Light" - Seyranyan, Lilit (Bulletin of Yerevan University B: Philology, 2025)
The purpose of the research is to define and analyze the sign system of the collection "Let there be Light" by P. Sevak, expressing closeness, formed as a result of Soviet ideological restrictions and conditioned by the introspective aspirations of the author. Consistently solved research tasks involve identifying signs expressing closeness, thematic and ideological separation, clarifying their commonality, and identifying systemic features. Signs of closeness on an introspective basis are also revealed in the cycle "You don’t love anew, you love again", forming self-reflective images of longing for oneself, reconciliation with oneself, self-denial, introspection and self-pity, self-deception, self-love and "suicide" and other artistic manifestations of closeness and stiffness. Among them, images of a closed door of a loved one, woman as a reserve, the inaccessibility of a woman with the features of the Mother of God, the apparent certainty and indefinite infinity of the horizon image, the dilemma between duty and feelings can be considered. Sevak's famous formula " You don’t love anew, you love again " is also seen as an image of a vicious circle.The relevance of the research is due to the modern methodological approach - a combination of structural-semiotic and mythocritical methods, as well as the need to choose a new perspective in the study of the ideological and aesthetic system of Sevak's well-studied collection "Let there be Light" and the formulation of a new interpretative hypothesis.
Keywords: P. Sevak; "Let there be light"; closeness; sign; introspection; reconciliation with oneself; woman as a reserve; longing, self-reflection; duty; love